1998
DOI: 10.1359/jbmr.1998.13.7.1191
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Ovarian and Gonadotropin Hormone Levels in Premenopausal Women with Low Bone Mass

Abstract: We hypothesized that lower ovarian and gonadotropin hormone concentrations would be associated with lower levels of peak bone mineral density (BMD) in apparently normally menstruating women who did not exercise intensively and did not report anorexia or bulimia. This hypothesis was evaluated using a case-with-control study design (n = 65) which was nested within a population-based longitudinal study of peak bone mass (Michigan Bone Health Study) with annual assessment in women aged 25-45 years (n = 582). Cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 29 publications
2
41
0
2
Order By: Relevance
“…Those other studies used the basal body temperature method, which has been shown to be an unreliable method of determining ovulation and which may have led to misclassification (48 -50). Indeed, those investigators reported a much higher prevalence of ovulatory disturbances (67-80% of participants had disturbances) (7, 10) than we and others (12,51) who used progesterone measurements have reported. Both salivary and urinary progesterone are highly correlated with serum progesterone, and measuring them is a reliable method of assessing ovarian function (28,30,52).…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Those other studies used the basal body temperature method, which has been shown to be an unreliable method of determining ovulation and which may have led to misclassification (48 -50). Indeed, those investigators reported a much higher prevalence of ovulatory disturbances (67-80% of participants had disturbances) (7, 10) than we and others (12,51) who used progesterone measurements have reported. Both salivary and urinary progesterone are highly correlated with serum progesterone, and measuring them is a reliable method of assessing ovarian function (28,30,52).…”
Section: Discussionmentioning
confidence: 47%
“…Prior et al (10) proposed that the observed bone loss was due to reduced luteal progesterone production in the presence of normal concentrations of estrogen, but this possibility has not been supported by other investigators. Sowers et al (51) found lower concentrations of both luteal phase estrogen and progesterone urinary metabolites in women with BMD in the bottom 10th percentile than in women with BMD in the 50 -75th percentile. DeSouza et al (11) observed lower luteal phase progesterone in women with short luteal phases (but found no difference in BMD) than in women with normal luteal phases.…”
Section: Discussionmentioning
confidence: 97%
“…Correction of the urinary hormone value with creatinine excretion reduces within women variations in hormone concentrations, which can be considerable (25). Preservation of urine with glycerol is required to maintain gonadotropin activity in some (31) but not all (35) assays.…”
mentioning
confidence: 99%
“…Esta diminuição do estradiol foi anteriormente relatada por Sowers e cols. em um grupo de mulheres jovens, pré-menopausadas e com osteoporose de fêmur sem etiologia definida (12). Em um subgrupo de pacientes, nas quais foi realizado DMO por fazerem parte de grupos controle de outros estudos realizados em nosso serviço, nenhuma causa secundária foi identificada pela avaliação inicial.…”
Section: Fator Etiológico Pacientes (N= 34)unclassified